2021
DOI: 10.22159/ijap.2021v13i5.42175
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and Evaluation of Transdermal Patches of Pantoprazole Sodium

Abstract: Objective: The present study was an attempt to develop an alternative dosage form for the existing conventional oral, parenteral proton pump inhibitor (PPI) as transdermal patches for treating peptic ulcers. Methods: Transdermal patches of PPI were prepared using HPMC E5 with PVP K 30 and HPMC E5 with Eudragit L100 polymers in different ratios by a solvent evaporation method. All the formulated patches were subjected to various evaluation parameters such as thickness, folding endurance, weight uniformity, cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…The formation of the complex can be determined by IR spectroscopy by comparing the spectrum of the complex or conjugate of a drug with the spectrum of each individual component and its mechanical mixture. Stability of pharmacosomescan is characterized by comparing the spectrum of its microdispersion in water after lyophilisation at different time intervals [20].…”
Section: Complex Determinationmentioning
confidence: 99%
“…The formation of the complex can be determined by IR spectroscopy by comparing the spectrum of the complex or conjugate of a drug with the spectrum of each individual component and its mechanical mixture. Stability of pharmacosomescan is characterized by comparing the spectrum of its microdispersion in water after lyophilisation at different time intervals [20].…”
Section: Complex Determinationmentioning
confidence: 99%
“…The patch weights were weighed using an analytical balance, where for every 3 patches, the average weight and standard deviation were determined (7,(11)(12)(13)(14).…”
Section: Weight Uniformitymentioning
confidence: 99%
“…Testing of Folding endurance is carried out with the patch repeatedly in the same position until the patch. The number of folds is considered as the value of resistance to folding (7,(11)(12)(13)(14).…”
Section: Folding Endurancementioning
confidence: 99%
See 1 more Smart Citation
“…It was concluded that patches with composition Eudragit L100: HPMC E5 (1:1) provided best results. 9 Rasool et al (2021), prepared dimenhydrinate transdermal patch utilizing various combination of polymers viz. Eudragit S100, Ethylcellulose, HPMC and PVP.…”
Section: Introductionmentioning
confidence: 99%